Larvicidal Effectiveness of Azolla pinnata against Aedes aegypti (Diptera: Culicidae) with Its Effects on Larval Morphology and Visualization of Behavioural Response. (27th June 2018) - Husna Zulkrnin, Nor Shaida; Rozhan, Nurul Nadiah; Zulkfili, Nur Amanina; Nik Yusoff, Nik Raihan; Rasat, Mohd Sukhairi Mat; Abdullah, Nor Hakimin; Ahmad, Muhammad Iqbal; Ravi, Rajiv; Ishak, Intan H.; Mohd Amin, Mohamad Faiz
Abstract : Dengue is vector-borne diseases with 390 million infections per year extending over 120 countries of the world. Aedes aegypti (L.) (Diptera: Culicidae) is a primary vector for dengue viral infections for humans. Current focus on application of natural product against mosquito vectors has been the main priority for research due to its eco-safety. The extensive use of chemical insecticides has led to severe health problems, environmental pollution, toxic hazards to human and nontarget species, and development of insecticide resistance on mosquitoes. Azolla pinnata is an aquatic fern and predominantly used as feed in poultry industry and as fertilizer in agricultural field for enhancing the fertility of rice paddy soil. The present study was conducted to explore the larvicidal efficacy of A. pinnata using fresh and powdered form against late third-stage larvae (6 days, 5 mm in larvae body length) of Ae. aegypti (L.) (Diptera: Culicidae). The larvicidal bioassays were performed using World Health Organization standard larval susceptibility test method for different concentration for powdered and fresh A. pinnata. Powdered A. pinnata concentration used during larvicidal bioassay ranges from 500ppm to 2000ppm; meanwhile, fresh A. pinnata ranges from 500ppm to 9, 000, 000 ppm. The highest mortality was at 1853 ppm for powdered A. pinnata compared with fresh A. pinnata at 2, 521, 535 ppm, while the LC50 for both powdered and fresh A. pinnata recorded at 1262 ppm and 1853 ppm, respectively. Finally, the analysis of variance (ANOVA) showed significant difference on Ae. aegypti larval mortality (F=30.439, df=1, p≤0.001) and concentration (F=20.002, df=1, p≤0.001) compared to powdered and fresh A. pinnata at 24-hour bioassay test. In conclusion, the powdered A. pinnata serves as a good larvicidal agent against Ae. aegypti (L.) (Diptera: Culicidae) and this study provided information on the lethal concentration that may have potential for a more eco-friendly Aedes mosquito control program.